CONTEMPORARY MARKETING MIX, BRAND IMAGE AND CONSUMER BUYING INTEREST IN ISLAMIC BANKING - Wenda Wahyu Christiyanto (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
In the last 20 years, Islamic Banking has been operating in Indonesia. It Begun when Bank Muamalat Indonesia established in 1992, then followed by others. With over 250 million populations in Indonesia, including a large number of muslim as majority, Indonesia should be a potential market for Islamic Banking. However, Islamic Banks, which is supposed to be muslim icon, are not capable to do much in the largest muslim population country. Over than two decades, Islamic Banks still have not been able to offset the domination of Conventional Banks, it just only have around 5 percent of banking market share. Based on the phenomenon, this study aims to examine the Islamic Banks viewed from the marketing aspect. This research was conducted in East Java, because this region has a large number Muslim population with a thick Islamic culture. This study aims to determine the effect of contemporary marketing mix on the interest of east java’s resident, become customers of Islamic Banks, with brand image as the mediator variable. This research was conducted by survey method, then the data obtained were analyzed by SEM-PLS technique using WarpPLS 5.0. The result show that the data has met the rules of outer model, inner model, model fit and quality indices. The results in the study indicate that contemporary marketing mix affects the East Javas’s resident’s interest, become a customer of Islamic Banks, with brand image as partial mediator variable.